2019
DOI: 10.1371/journal.pone.0212327
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of conflicts of interest and of sponsorship of guidelines in anaesthesiology. A cross-sectional study

Abstract: Guideline recommendations may be biased due to conflicts of interest (COI) of panel members and sponsorship of the guideline. Potential impact of COI, and their management, should be transparently reported. We analysed 110 guidelines published in ten anaesthesia journals from 2007 to June 2018. We report on the number (%) that 1) published COI disclosures; 2) in a distinct paragraph; 3) described and explained the COI of panel members, and 4) of the Chairperson; 5) reported and described the presence or absenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Nevertheless, Wyssa et al found that there was no disclosure of authors' conflicts of interest in 36% of clinical guidelines published in ten high-impact anesthesiology academic journals between 2008 and 2018. [48] Additionally, some studies in other specialties found that there were large amounts of undeclared and under-declared financial relationships between the healthcare industry and influential physicians. [49] Further transparency in financial relationships between the healthcare industry and the influential physicians is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, Wyssa et al found that there was no disclosure of authors' conflicts of interest in 36% of clinical guidelines published in ten high-impact anesthesiology academic journals between 2008 and 2018. [48] Additionally, some studies in other specialties found that there were large amounts of undeclared and under-declared financial relationships between the healthcare industry and influential physicians. [49] Further transparency in financial relationships between the healthcare industry and the influential physicians is needed.…”
Section: Discussionmentioning
confidence: 99%